Lesson Plan for Elementary School Learning Based on Higher Order Thinking Skills - Agustina Wahyuningsih; Bambang Sumardjoko; Anatri Desstya; Minsih; Choiriyah Widyasari (Universitas Pendidikan Ganesha, 2023)
The importance of developing higher-order thinking skills in the 21st century impacts the standardization of learning tools in schools. This research analyses the lesson plans prepared using the HOTS-based learning plan indicators. The research design used is document analysis. The data source in the study was the lesson plans that elementary school teachers had prepared, as many as 4 lesson plans—data collection techniques using documentation and interviews. Data analysis techniques are data reduction, display, and verification. The study results showed that the HOTS aspect was included in the lesson plan the teacher had prepared. Namely, the competency selection aspect was 83.3%. Formulation of indicators by 25%. The identity of the selection of learning materials is 100%. The formulation of learning objectives is 50%, the use of learning methods is 75%, and the use of learning resources is 75%. The use of learning media is 100%. Learning activities by 100%, selection of assessment by 100%. Overall the coverage of lesson plans analyzed on HOTS was 80.2%. The HOTS-based learning plans that elementary school teachers have prepared still need to improve their preparation, especially in using HOTS verbs. A review of the HOTS-based learning implementation plan is needed to achieve learning activities that refer to developing students' higher-order thinking skills.